VALIDITAS APLIKASI PEMBELAJARAN MATEMATIKA ANMATH UNTUK MENINGKATKAN LITERASI NUMERASI SISWA - Diah Ayu Cahyani, Paramodyta; Nanang Khuizaini (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This study aims to develop and evaluate the validity of the mathematics learning application "ANMATH," designed to improve students' numeracy literacy. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation), focusing on the first three stages: analysis, design, and development. The subjects of the study consisted of 11th-grade science students from class XI MIPA 2 at SMA Negeri 1 Sedayu, two subject matter expert validators, and two media expert validators. Data were collected through observation, interviews, questionnaires, and numeracy literacy skills tests. The validation results show that the ANMATH application received an average score of 52.5 with a very valid criterion from subject matter experts and an average score of 76.5 with a very valid criterion from media experts. Thus, this application meets the criteria for excellent validity and is suitable for further testing, including practicality and effectiveness tests. This research is expected to contribute to providing effective learning media to enhance students' numeracy literacy.